Kebijakan Penanggulangan Kemiskinan di Era 4.0: Studi Konten Analisis New Media Pemerintah Kota Magelang - Dedi Setiawan; Rutiana Dwi Wahyunengseh (Social and Political Science Faculty - Universitas Tidar, 2020)
The use of ICT in the public sector has been widely applied in various countries including Indonesia. One of the goals is to make it easier to disseminate policies to the public. From the practice level, the use of new media / social media in Indonesia has been regulated in a law. The city of Magelang is one of the cities that applies the use of ICT to support public services and is considered successful by the central government so that it has received various awards. However, in Magelang City, the problem of poverty is still a priority to be resolved. This study aims to describe the use of ICT types of social media by the Magelang City Government in disseminating poverty issues and to analyze the extent to which Magelang City is prepared to utilize social media to disseminate poverty issues. The qualitative research method is content analysis research with data collection in the form of content content analysis, documentation, and interviews with purposive techniques. Data were analyzed using content analysis by krippendorf. The results of the study show that the government of Magelang City has not used social media to disseminate poverty reduction policies. This can be seen from; (i) social media management related to the proportion of content issues uploaded on social media that shows dissemination related to poverty issues has not been specifically planned to be published, seen from the very small number of posts related to poverty issues, (ii) government responses in response to comments and questions from followers tend not respond so that the use of social media still goes in one direction. Thus, ICT has not played a role in its social aspects for information dissemination, social learning, dialogue, and networking. This can be seen from; (i) there is no strategy in managing content and monitoring evaluation to see the growth of followers, (ii) the response of followers / society still tends to be passive by only giving likes to government-owned social media uploads that are one-way in nature.